Brazilian Adults’ Hope and Spirituality in Preoperative Heart Surgery: A Cross-Sectional Study - Juciano Augusto da Silva Negré; Leonardo Santos de Souza; Elaine Cristina Negri (Brazilian Journal of Cardiovascular Surgery, 2023)
ABSTRACT Introduction: Given the incipience of domestic studies on hope and spirituality in cardiology, this study evaluated adult cardiac patients’ hope in the preoperative period of cardiac surgery and its potential association with spirituality. Methods: This is a cross-sectional study carried out at a university hospital in the State of São Paulo (Brazil). A total of 70 patients answered the Herth Hope Scale and a sociodemographic questionnaire before undergoing surgical procedure between January and October 2018. Descriptive and inferential analyses were performed using the Spearman’s rank correlation coefficient and the Mann-Whitney U test. The R-3.4.1 software and SAS System for Windows 9.2 were also used. P-value < 0.05 was considered statistically significant. Results: Patients had a high prevalence of modifiable risk factors. Having a religion (37.53±4.57) and practicing it (38.79±4.25), regardless of its denomination and time dedicated to that religion, was associated with hope (P<0.01) in the immediate preoperative period of cardiac surgery. However, hope did not exhibit a significant correlation with factors such as age (P=0.09) and time dedicated to religious practice (P=0.07). Conclusion: Regardless of the religious strand and time dedicated to religious practices as an expression of spirituality, hope was associated with the participants’ religion and religiosity. Considering the importance of this construct on the processes of health and disease, the whole health team should consider in their praxis a setting of conditions to make the patient’s spirituality process feasible during hospitalization.